Isolation and Identification of Cryptococcus neoformans from Human Skin Lesions and Application of Animal Experiment (in vivo): Mahmood F.A and Alwan M.J - A., Mahmood F. (The Iraqi Journal of Veterinary Medicine, 2015)
The study aimed at determining the percentage of Cryptococcus neoformance isolated from skin lesions in human in order to find the effect of heat killed cryptococcal antigen on infection with this fungus in mice and efficiency of chitosan in protecting the mice against the infection with the fungus Cryptococcus neoformance. In order to achieve the first aim, 100 cutaneous samples were collected from variable skin regions in humans suffering from cutaneous lesions from both sexes and with variable ages. The samples were collected from Abu-Ghraib Hospital,Al-Yarmook Teaching hospital and Al-karama Hospital during a period from December 2012 untill March 2013. The results showed that 3 (3%) isolates out of 100 skin samples were the fungus C.neoformans. The fungal isolates were from patients with average age 1-25 years they did not have any systemic clinical signs. Also the results showed that the ratio of fungal isolates from females was higher than those isolated from males. In order to achieve the second aim ,Sixty white mice from both sexes and with average age 8-10 weeks were divided randomly into 4 groups equally and treated as follows 1st group was immunized with 0.2 ml of heat killed C.neoformans antigens (HKCAgs) in a dose of (1X107) fungal cells,subcutanously at two doses with two weeks interval. The 2nd group was immunized similar to 1st group and at the same time fed diet supplemented with 1g\kg diet of chitosan for 8 weeks. While the 3rd group served as control positive group, 4th group served as control negative group.Cell mediated and antibody mediated immune responses were determined at day 27-30 post-immunization. Immunized animals fed diet supplemented with chitosan showed higher values of delayed type hypersensitivity reaction and Abs titer compared with those values of immunized animals only.